2021
DOI: 10.1097/cm9.0000000000001653
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Dbf2-related Kinase 1 functions as tumor suppressor in glioblastoma by phosphorylation of Yes-associated protein

Abstract: Background: The Nuclear Dbf2-related (NDR1) kinase is a member of the NDR/LATS family, which was a supplementary of Hippo pathway. However, whether NDR1 could inhibit glioblastoma (GBM) growth by phosphorylating Yes-associated protein (YAP) remains unknown. Meanwhile, the role of NDR1 in GBM was not clear. This study aimed to investigate the role of NDR1-YAP pathway in GBM. Methods: Bioinformation analysis and immunohistochemistry (IHC) were performed to identify the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Ser-436 phosphorylation promoted YAP-mediated GBM proliferation, migration, and invasion [ 60 ]. NDR1 inhibited GBM progression by phosphorylating YAP [ 61 ]. PIKE-A regulated STAT3 phosphorylation-mediated G6PD expression to promote GBM cell proliferation and anti-ROS stress response [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ser-436 phosphorylation promoted YAP-mediated GBM proliferation, migration, and invasion [ 60 ]. NDR1 inhibited GBM progression by phosphorylating YAP [ 61 ]. PIKE-A regulated STAT3 phosphorylation-mediated G6PD expression to promote GBM cell proliferation and anti-ROS stress response [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a pan-cancer analysis of STK38 reveals that the expression of STK38 is associated with patient survival, immune cell infiltration such as NK cells, cancer-associated fibroblasts, tumor mutation burden and microsatellite instability in several human cancers [ 66 ]. However, there is also evidence that STK38 can reduce the cell proliferation of glioblastomas and inhibit the metastasis of prostate cancer [ 67 ]. STK38/STK38L kinases phosphorylate the transcriptional coactivator yes-associated protein (YAP1) and thereby negatively regulate YAP1 transcriptional activity, suggesting that STK38/STK38L function as tumor suppressors [ 68 ].…”
Section: Involvement Of Stk38 In Malignancymentioning
confidence: 99%
“…Large tumour suppressor genes (Lats) can enhance the homeostasis of cells. Furthermore, it can mediate Hippo’s inhibitory signal [ 82 ]. Liu and Mei et al found that SUMO of Lats1 affects its kinase activity, especially Hippo signal transduction [ 64 ].…”
Section: The Role Of Protein Sumoylation In Hcc Progressionmentioning
confidence: 99%